Effect of Pallet Deckboard Stiffness on Corrugated Box Compression Strength. Issue 4 (28th March 2016) - Baker, Matthew; Horvath, Laszlo; White, Marshall
Abstract : The packaging industry has long considered pallets to be rigid structures. However, in a unit load, the weight of the product produces compressive forces that are distributed across the pallet causing the top deckboards to deflect. Corrugated paperboard boxes are highly susceptible to changing support conditions; therefore, the deckboard deflection directly impacts the vertical compression strength of the box. Therefore, the objective of this study is to evaluate the effect of pallet deckboard stiffness on the vertical compression strength and deflection of corrugated paperboard boxes. Additional treatments included gaps between the deckboards and location of the box relative to the pallet stringers. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : It was found that decreasing the deckboard stiffness reduced the compression strength of a box by as much as 26.4%. Additionally, changing the location of a box relative to the stringer was found to reduce compression strength by an additional 15.3% when only two corners were directly over the stringer. The effect of gaps between deckboards was found to have a more complex interaction that decreased the effect of deckboard stiffness.